Local application of MDL28170-loaded PCL film improves functional recovery by preserving survival of motor neurons after traumatic spinal cord injury. (16th February 2019) - Shi, Dongling; He, Teng; Tang, Weijian; Li, Heyangzi; Wang, Chao; Zheng, Mingzhi; Hu, Jue; Song, Xinghui; Ding, Yuemin; Chen, Ying-ying; Shen, Yueliang; Jin, Hongfeng; et al.
Highlights: PCL film shows no toxic, neuron adhension characteristic. MDL28170(<50 μM) increases VSC4.1 motor neuronal cell viability in vitro . MDL28170-loaded PCL film slowly releases MDL28170. MDL28170-loaded PCL film improves functional recovery in SCI rats. Abstract: Neuronal death and organization degeneration can happen inordinately after spinal cord injury (SCI), which lead to nerve dysfunction. We aimed to determine whether local application of a cell permeable calpain I inhibitor (MDL28170) can promote SCI recovery by increasing neuronal cell viability. MDL28170-loaded polycaprolactone (PCL) film was fabricated. Scanning electron microscopy showed the surface of PCL film was smooth with holes (diameter at μM level). The PCL film was non-toxic, biological compatibility, and had good neuron adhension and slow release characteristic. MDL28170 increased VSC4.1 motor neurons' viability under tunicamycin (an endoplasmic reticulum stress) induced injury. In a traumatic SCI rat model, MDL28170-loaded PCL film reduced the area of lesion cavity, and promoted recovery of locomotor behavior. Moreover, the expression of GAP-43 was upregulated after MDL28170-loaded PCL film treatment. Thus, our findings demonstrated that localized delivery of MDL28170 could promote SCI recovery by inhibiting endoplasmic reticulum stress, preserving survival of the motor neurons, which may point out a promising therapeutic target for treating SCI patient.